Beyond racial gridlock : embracing mutual responsibility - Yancey, George A., 1962- (Downers Grove, Ill. : InterVarsity Press, 2006)
Sociologist George Yancey surveys a range of approaches to racial healing that Christians have used and offers a new model for moving forward. The first part of the book analyzes four secular models regarding race used by Christians (colorblindness, Anglo-conformity, multiculturalism and white responsibility) and shows how each has its own advantages and limitations. Part two offers a new "mutual responsibility" model, which acknowledges that both majority and minority cultures have their own challenges, tendencies, and sins to repent of, and that people of different races approach racial reconciliation and justice in differing but complementary ways.
Part I: Four secular models of dealing with racism -- Two views of racism -- Colorblindness -- Anglo-conformity -- Multiculturalism -- White responsibility -- Part II: Finding a Christian approach to dealing with racism : the mutual responsibility model -- Toward constructing a Christian solution to the problem of race -- Sin nature and European Americans -- Sin nature and racial minorities -- Jesus : the ultimate reconciler -- The fear factor -- What would a Christian solution look like?
Includes bibliographical references (p. [179]-197).
Keywords: Race relations -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; United States -- Race relations